Qualitative assessment of bioethanol production sustainability applying the GBEP methodology: a comparative case between coconut husks and sugarcane bagasse (Research, Society and Development, 2022)
The conventional production of bioethanol takes place through sugar cane processing. Given that Brazil generates abundant lignocellulosic residues, other bioethanol production routes from residual biomasses have been increasingly considered. In this context, this study aimed to assess the sustainability of two second-generation bioethanol (E2G) production routes, one from sugarcane bagasse and the other from coconut husks. To this end, nine indicators proposed by the GBEP (Global Bioenergy Partnership) methodology, namely GHG emissions, non-GHG emissions, water use and efficiency, income changes, bioenergy sector jobs, incidence of occupational injuries, illnesses and deaths, productivity, net energy balance and increased gross value from bioenergy production, were applied. Following the two bioethanol production route assessments through indicator application, a conclusive graphic outlook was constructed to identify the most sustainable route. The sugarcane bagasse production route derives from the Iogen technology and is employed at Raízen's Costa Pinto Plant, which produces this biofuel on an industrial scale, while the coconut husk production route is currently being improved on a bench scale. The indicator analysis demonstrates that, despite the coconut husk route exhibiting greater social sustainability, with better employee remuneration and less frequent injuries, illnesses and occupational deaths, the sugarcane bagasse route shows greater environmental and economic sustainability, due to lower GHG emissions and water extraction, besides higher productivity, and higher net production income. Therefore, the comparative analysis produced by applying the GBEP methodology demonstrates that the sugarcane bagasse route is the most sustainable regarding the production of second-generation bioethanol.